Title: Research on the Positive Impact of Dance Creation and Performance EdCreating a Stage for Performing Creative Dance Experiments in the Classroom of the Tian Tian Institute Jiangsu Province China - Guo, Ruiyi; Mooosuwan, Thanyalak (Chophayom Journal, 2024)
Dance education plays an irreplaceable role in cultivating aesthetic sensibilities, physical fitness, and cultural literacy. This paper focuses on exploring the importance of dance creation and performance in the holistic development of students in training institutions, including the cultivation of creativity, self-confidence, physical coordination, aesthetic ability, and social skills. The study indicates that dance, as an art form, also has a positive impact on students' mental health and the broadening of their career pathways. Through qualitative research methods, including in-depth interviews and field observations, this study systematically analyzes the educational outcomes of dance creation and performance at Tiantian Education Institution. The results show that dance education not only improves students' physical fitness and artistic literacy but also significantly enhances their self-confidence and creativity. Furthermore, the study finds that the professional teaching environment and resources in training institutions are crucial to the development of students' teamwork and social skills. This research provides empirical evidence for the role of dance education in promoting the holistic development of students and highlights its importance in the modern education system. Keywords: Choreography, Dance Performance